The Effect of Company Fundamentals on Sharia Stock Prices with Earning Per Share as a Moderating Variable in Jakarta Islamic Index 70 Period 2018-2021 - Fathia, Sakina; Yahya, Idhar; Siregar, Narumondang Bulan (Journal of Social Science, 2023)
An investor who wants to invest must consider his investment goals, by looking at the range of the length of time to anticipate risks that may occur as little as possible. So the most important thing for investors is to understand what investment instruments are suitable and will be chosen to be used in investing, and to achieve the purpose of the investment itself, namely the acquisition of profits in the future. In this study the author used quantitative descriptive method. Quantitative research according to Sujarweni (2021: 39) is a type of research that produces findings that can be achieved using statistical procedures. Meanwhile, according to Sujarweni (2021: 39), quantitative research is a process to find knowledge that uses data in the form of numbers as a tool to analyze information about what you want to know.